Analyzing the Impact of Environmental Performance and Profit Growth on Firm Value in Indonesia’s Oil, Gas, and Coal Sector - Khalifah Shela Sardila; Januar Eko Prasetio (International Journal of Applied Business and International Management, 2025)
Corporate value is an important indicator in assessing a company’s performance and competitiveness in the market. In the context of the oil, gas, and coal sectors—industries particularly vulnerable to environmental concerns—attention to sustainability is becoming increasingly critical. This study aims to analyze the effect of environmental performance and profit growth on the firm value of companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. A quantitative method with a correlational design was used, drawing on secondary data from annual and sustainability reports. A purposive sampling technique yielded 31 companies that met specific criteria, including consistent listing on the IDX, complete reporting, and PROPER scores from the Ministry of Environment and Forestry. Environmental performance was measured using PROPER scores, profit growth by the net profit growth ratio, and firm value using Tobin’s Q. Data were analyzed using multiple linear regression, preceded by classical assumption tests for normality, multicollinearity, heteroscedasticity, and autocorrelation. The results show that environmental performance has a significant negative effect on firm value (? = -0.996; p 0.001), while profit growth is not statistically significant (? = 0.033; p = 0.058)